Compartmentalized Jet Polymerization as a High‐Resolution Process to Continuously Produce Anisometric Microgel Rods with Adjustable Size and Stiffness. Issue 49 (17th October 2019) - Krüger, Andreas J. D.; Bakirman, Onur; Guerzoni, Luis. P. B.; Jans, Alexander; Gehlen, David B.; Rommel, Dirk; Haraszti, Tamás; Kuehne, Alexander J. C.; De Laporte, Laura
Abstract: In the past decade, anisometric rod‐shaped microgels have attracted growing interest in the materials‐design and tissue‐engineering communities. Rod‐shaped microgels exhibit outstanding potential as versatile building blocks for 3D hydrogels, where they introduce macroscopic anisometry, porosity, or functionality for structural guidance in biomaterials. Various fabrication methods have been established to produce such shape‐controlled elements. However, continuous high‐throughput production of rod‐shaped microgels with simultaneous control over stiffness, size, and aspect ratio still presents a major challenge. A novel microfluidic setup is presented for the continuous production of rod‐shaped microgels from microfluidic plug flow and jets. This system overcomes the current limitations of established production methods for rod‐shaped microgels. Here, an on‐chip gelation setup enables fabrication of soft microgel rods with high aspect ratios, tunable stiffness, and diameters significantly smaller than the channel diameter. This is realized by exposing jets of a microgel precursor to a high intensity light source, operated at specific pulse sequences and frequencies to induce ultra‐fast photopolymerization, while a change in flow rates or pulse duration enables variation of the aspect ratio. The microgels can assemble into 3D structures and function as support for cell culture and tissue engineering. Abstract : Compartmentalized microfluidic jet gelation allows for the continuous high‐throughput fabrication of anisometric microgel rods with adjustable aspect ratio and stiffness. High‐frequency laser pulses initiate local ultrafast photopolymerization in the jet leading to microgels with rod diameter significantly smaller than the channel diameter to overcome the size limits of established microfluidic plug flow gelation.